Age and group residence but not maternal dominance affect dominance rank in young domestic horses - Komárková, M; Bartošová, J; Dubcová, J (Journal of animal science, 2014)
We present a study focused on those factors influencing dominance position in young horses, with emphasis on the role of the mother. Horses, as other group-living polygynous mammals, form stable linear dominance hierarchies based on agonistic interactions. Higher dominance positions are believed to be connected, in both sexes, to better condition and higher reproductive success. Many variables play a role in forming the dominant-submissive relationships between horses; however, the maternal effect on the dominance position of the offspring still remains unclear, as do the possible mechanisms of transference ("inheritance"). We hypothesized that the maternal dominance position, plus differences in suckling parameters or maternal style, may be responsible for later outcome of the offspring's dominance position, characterized by 2 variables: index of fighting success (CB); and rate of winning encounters (RW). Our study animals were 8 groups of Kladruby horses, loose-housed lactating mares with foals (n = 66 mare-foal pairs); and subsequently 4 groups of the same foals at 3 yr of age. Our results revealed the impact of age on the dominance position of the young horses (P < 0.001 for CB, and P < 0.01 for RW), and residence in the group (P < 0.01, P < 0.01, respectively); not the maternal dominance position. Older foals reached higher dominance positions, independent of the dominance position, age, or experience of the mother; therefore, we did not find support for direct inheritance of maternal rank. Nevertheless, the foals born to the same mare in 2 consecutive seasons (n = 16 mares) revealed fair repeatability in the dominance position they obtained at 3 yr of age (intraclass correlation coefficient = 0.46). This suggests an important constant effect of the mother on the social success of her progeny; however, we did not find a significant effect of any of the tested variables describing maternal characteristics or maternal care. Dominance position depended significantly on the foal's age at observation, and the residence in the herd formed via sequential introducing of later-weaned groups of foals. The most dominant horses were mainly recruited from the first-weaned group of the season, and thus were also the oldest individuals in the herd. Further research is needed to discover the role of foal personality and mare style, and their links to possible dominance behaviors in a herd.
Keywords: agrese; Female; Maternal Behavior; Social Dominance; Animals; laktace; mare; Aggression; dominance rank; chování zvířat; residence; mateřské chování; mužské pohlaví; Weaning; sociální chování; stárnutí; Lactation; individuality; Siblings; Male; sociální dominance; koně; Aging; zvířata; Behavior, Animal; Horses; ženské pohlaví; odstavení; Social Behavior; horse; age; sourozenci